An evaluation tool for Age-Friendly and Dementia Friendly Communities. Issue 1 (24th January 2018) - Buckner, Stefanie; Mattocks, Calum; Rimmer, Melanie; Lafortune, Louise
Abstract : Purpose: The purpose of this paper is to report how an evaluation tool originally developed for Age-Friendly Cities was pilot-tested in the context of the Dementia Friendly Community (DFC) initiative of the city of Sheffield/UK. It presents finding and outputs on which other communities with dementia friendly agendas can draw. Design/methodology/approach: The original evaluation tool was adapted to a focus on dementia friendliness. Data collection involved scoping conversations, documentary analysis, interviews and group discussions. Following evidence appraisal, Sheffield's approach to dementia friendliness was assessed. A local steering group was central to the study. Findings: The evidence indicates areas of strength in Sheffield's approach to dementia friendliness: involvement of older people; service provision; collaboration; monitoring and evaluation. Scope for improvement was identified around resource allocation, and use of existing guidance on dementia friendliness. Recommendations for policy and practice include enhancing pooling of resources, more detailed recording of resources allocated to dementia-related activity, and collection of evidence on how people affected by dementia have shaped the city's DFC initiative. Key research outputs are an adaptable logic model and an emerging evaluation framework for DFCs. Research limitations/implications: The study was a short pilot with limited resources. Its findings and outputs must be considered preliminary. Originality/value: The findings and outputs provide a basis for further research. The study has suggested key components of an evaluation framework for DFCs. It is informing ongoing work to develop such a framework.